Mechanism Role of Investment Strategies for Investment Performance: Investigating the Impact of Personality Traits: A Case of Behavioral Finance - Tariq Mahmood Shaikh; Syed Zain ul Abdin (Journal of Accounting and Finance in Emerging Economies)
Purpose: This study investigates the mechanism role of investment strategies in mediating the relationship between personality traits and investment performance within the behavioral finance framework. Drawing upon the Big Five personality models and established investment analysis approaches, this research examines how individual differences in personality characteristics influence investment strategy preferences and subsequent performance outcomes among individual investors.